Healthcare and productivity loss costs in young adults after bacterial meningitis: a cross-sectional follow-up study - Omaima El Tahir; Sanne Vrijlandt; Jelle de Jongh; Rogier C J de Jonge; Sui Lin Goei; Jeroen Pronk; Anne Marceline van Furth (BMJ Paediatrics Open)
Objective To determine healthcare and productivity loss costs among young adult survivors of childhood bacterial meningitis (BM).Methods In this cross-sectional study, online versions of the Institute for Medical Technological Assessment (iMTA) Medical Consumption Questionnaire and the iMTA Productivity Costs Questionnaire were used to measure healthcare consumption and productivity loss costs in young adult survivors of childhood BM. Mean healthcare and productivity loss costs were calculated and the differences in costs across subgroups based on age at onset, sex and causative pathogens were investigated.Results A total of 454 patients were included in the cost analysis of healthcare utilisation and a total of 471 patients were included in the cost analysis of productivity losses. The 3-month mean societal cost per patient amounted to €4985.32 (median €1363.71, IQR €576.04–€2948.67), of which €4790.84 (median €1125.90, IQR €271.20–€2489.54) was due to productivity losses. Productivity loss costs were significantly higher in survivors of childhood BM caused by Streptococcus pneumoniae compared with survivors of childhood BM caused by Neisseria meningitidis.Conclusions This study highlights the potential significant economic burden in young survivors of childhood BM and emphasises the possible impact of very long-term sequelae. In particular, very long-term sequelae of BM contribute to indirect costs. To the best of our knowledge, this is the first study to investigate the societal costs of childhood BM over a two-decade follow-up period. Further research into societal costs in young adult survivors of neonatal meningitis is needed to provide additional insights into the economic burden of childhood BM.